Regulatory T cells and transplantation tolerance: Emerging from the darkness?. Issue 7 (16th May 2021) - Waldmann, Herman
Abstract: The field of tissue transplantation has revolutionized the treatment of patients with failing organs. Its success, thus far, has depended on combinations of immunosuppressive drugs that damp host immunity, while also imposing numerous unwanted side‐effects. There is a longstanding recognition that better treatment outcomes, will come from replacing these drugs, fully or in part, by taking advantage of tractable physiological mechanisms of self‐tolerance. The past 50 years have seen many advances in the field of self‐tolerance, but perhaps, the most tractable of these has been the more recent discovery of a subset T‐cells (Treg) whose role is to regulate or damp immunity. This article is intended to first provide the reader with some historical background to explain why we have been slow to identify these cells, despite numerous clues to their existence, and also to indicate how little we know about how they achieve their regulatory function in averting transplant rejection. However, as is often the case in immunology, the therapeutic needs often dictate that our advances move to translation even before detailed explanations of the science are available. The final part of the article will briefly summarize how Treg are being harnessed as agents to interface with or perhaps, replace current drug combinations. Abstract : Regulatory T‐cells are being widely investigated for their therapeutic potential in harnessing immune‐tolerance processes, so reducing the need for potentially toxic drugs. The review aims to summarize what we know and what we do not know about these cells, and how they might be clinically harnessed to aid transplantation.